PENGEMBANGAN KOMIK DIGITAL PELESTARIAN LINGKUNGAN BERBASIS NILAI KARAKTER RELIGI UNTUK PEMBELAJARAN TEMATIK PADA SISWA SEKOLAH DASAR - fauzatul ma'rufah rohmanurmeta; Candra Dewi (Universitas Muhammadiyah Ponorogo, 2019)
ABSTRACTThe lack of maximum utilization of technology as a learning medium is directly proportional to the cultivation of the value of religious character in thematic learning, especially science subjects. Students are expected to learn and preserve the surrounding environment which is the creation of Allah SWT. Therefore, it is necessary to integrate technology with character values in the form of the development of digital comics for environmental preservation based on character values. This study aims to produce and know the validity of environmental conservation digital comic learning media based on the value of religious characters. The data obtained is qualitative and quantitative data. The test results of digital preservation comic learning media based on character values showed an average feasibility of 87% in material experts, 76% in media experts, 84.17% in classroom teachers, and 80.8% in students. Whereas for student learning outcomes obtained an average value of 84.83 from completeness criteria at least 75. These results indicate that the digital comic learning media of environmental conservation based on character value in integrative thematic learning is declared very feasible and ready to be implemented in thematic learning.